Haem oxygenase-1 induction reverses the actions of interleukin-1β on hypoxia-inducible transcription factors and human chondrocyte metabolism in hypoxia. - Clérigues, V; Murphy, C; Guillén, M; Alcaraz, M (2013)
HO-1 (haem oxygenase-1) catalyses the degradation of haem and possesses anti-inflammatory and cytoprotective properties. The role of inflammatory mediators in the pathogenesis of OA (osteoarthritis) is becoming increasingly appreciated. In the present study, we investigated the effects of HO-1 induction in OA and healthy HACs (human articular chondrocytes) in response to inflammatory cytokine IL-1 β (interleukin-1β) under hypoxic conditions. Hypoxia was investigated as it is a more physiological condition of the avascular cartilage. Hypoxic signalling is mediated by HIFs (hypoxia-inducible factors), of which there are two main isoforms, HIF-1α and HIF-2α. Normal and OA chondrocytes were stimulated with IL-1β. This cytokine suppresses HO-1 expression and exerts both catabolic and anti-anabolic effects, while increasing HIF-1α and suppressing HIF-2α protein levels in OA chondrocytes in hypoxia. Induction of HO-1 by CoPP (cobalt protoporphyrin IX) reversed these IL-1β actions. The hypoxia-induced anabolic pathway involving HIF-2α, SOX9 [SRY (sex determining region Y)-box 9] and COL2A1 (collagen type II α1) was suppressed by IL-1β, but importantly, levels were restored by HO-1 induction, which down-regulated TNFα (tumour necrosis factor α), MMP (matrix metalloproteinase) activity and MMP-13 protein levels. Depletion of HO-1 using siRNA (small interfering RNA) abolished the CoPP effects, further demonstrating that these were due to HO-1. The results of the present study reveal the different mechanisms by which HO-1 exerts protective effects on chondrocytes in physiological levels of hypoxia.